Efektivitas Problem Focused Coping Dalam Mengatasi Stress Belajar Siswa Pada Pelajaran Matematika - Idriani Idris; Abdulah Pandang (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2018)
The main problem examined in this research is students’ learning stress in Mathematics subject using Problem Focused Coping technique. The research aims at discovering (i) the degree of students’ learning stress in Mathematics subject before and after implementing Problem Focused Coping technique, (ii) the effectiveness of Problem Focused Coping technique in solving students’ learning stress in Mathematics subject at SMPN 1 North Galesong. The populations and samples of the research were class VIII students at SMPN 1 North Galesong of academic year 2015/2016 who were identified to experience stress in Mathematics subject with the total samples 38 students, consisted of 19 students were in the control group and 19 students were in the experiment group. The instruments used were questionnaire and observation. The data of the research were analyzed by using descriptive analysis and inferential statistics analysis with t-test. The result of the research reveal that (i) the degree of the students’ learning stress in Mathematics subject before implementing Problem Focused Coping technique is in high category; then, the students’ learning stress decreases after implementing Problem Focused Coping technique, which is in medium category, (ii) the Problem Focused Coping technique is effective in solving the students’ learning stress in Mathematics subject at SMPN 1 North Galesong.